Clinical and economic analysis of treatment sequences with prolgolimab and BRAF/MEK inhibitors in adult patients with metastatic or unresectable cutaneous melanoma - S. K. Zyryanov; K. V. Orlova (Фармакоэкономика)
Objective: evaluation of the comparative pharmacoeconomic effectiveness of treatment sequences with prolgolimab as the first line and combination therapy with BRAF/MEK inhibitors as the second line versus a regimen with BRAF/MEK inhibitors as the first line and prolgolimab as the second line in adult patients with metastatic or unresectable cutaneous melanoma.Material and methods. A detailed Markov and decision tree model was developed to allocate patients with metastatic cutaneous melanoma (mCM) with BRAF gene mutation (BRAF+) to treatment with prolgolimab or to targeted therapy with BRAF/MEK inhibitors (“dabrafenib + trametinib”, or “vemurafenib + cobimetinib” combinations). The costs of BRAF+ mCM therapy and the number of life years gained (LYGs) depending on the treatment regimen were calculated using approximated overall survival (OS) and progression-free survival (PFS) curves taken from relevant publications.Results. The treatment sequence for BRAF+ mCM had a significant impact on patient treatment outcomes: the median OS for the “prolgolimab → BRAF/MEK inhibitors” regimen was 41 months, while for the “BRAF/MEK inhibitors → prolgolimab” regimen it was 26 months; the median PFS was 11.5 months for the sequence starting with prolgolimab and 12.2 months for the strategy starting with “dabrafenib + trametinib” combination. The number of LYGs for a therapy regimen starting with prolgolimab and a regimen starting with “dabrafenib + trametinib” combination when modeling in the 1st year of therapy was 0.92 and 0.94 years, and at a 5-year horizon it was 3.19 and 2.75 years, respectively. At the same time, the cost of 1 LYG with a strategy starting with prolgolimab was 156 thousand rubles (5%) lower than the strategy starting with “dabrafenib + trametinib” combination.Conclusion. The developed pharmacoeconomic research model facilitated a clinical and economic analysis of using prolgolimab compared to targeted therapy with BRAF/MEK inhibitors across four lines of therapy, closely reflecting real clinical practice in the treatment of BRAF+ mCM patients.